Regional Economic Distress and Political Participation in National and European Parliamentary Elections in Western Europe - David K. Jesuit (Luxembourg Income Study (LIS), 2002)
This paper examines the relationship between regional or 'contextual' poverty, income inequality and unemployment and individual political participation in the mid-1990s for the following Western European countries: Belgium, France, West Germany, Italy, Spain, and the United Kingdom. This research is based on the notion that there are 'concentration effects' of poverty and unemployment that negatively affect the regional networks and structures facilitating individual political and economic participation (see Wilson, 1987; Cohen and Dawson, 1993). In exploring this connection, I construct regional poverty rates and inequality scores (the ratio of household income at the ninetieth and the tenth percentiles of the distribution) for these countries by aggregating the individual-level data made available through the efforts of the Luxembourg Income Study (LIS). Regional unemployment figures are from Eurostat (2000). I predict individual political participation in national elections and in the 1994 European Parliamentary election in a binary logistic regression analysis controlling for age, education, gender, individual household income and individual unemployment using data from the Eurobarometer (1994). I find evidence that individuals are less likely to vote in regions with higher levels of poverty and income inequality even beyond their individual economic and social circumstances. In sum, this research suggests that there are political consequences associated with regional economic distress that might threaten the maintenance of democracy and European enlargement in Europe.
Keywords: 330; Armut; Regionale Disparität; Regionale Einkommensverteilung; Regionaler Arbeitsmarkt; Demokratie; Belgien; Deutschland; Frankreich; Großbritannien; Italien; Spanien; Wahlbeteiligung